![(x - 9)(x + 9) (x - 9)(x + 9)](https://tex.z-dn.net/?f=%28x+-+9%29%28x+%2B+9%29)
Answers
Answered by
6
Answer:
(x - 9) (x + 9)
= (x² - 9²)
= x² - 81
__________
Identity used →
(a² - b²)
= (a + b)(a - b)
____________
Answered by
4
Given Algebraic Expression :
What to be Done : Simplify the Given Expression
Step by Step Solution :
We have a formula for calculating such problems And Now We can Substitute the values given in our Problem instead of
and
(Here a = x and b = 9)
(Using Formula
)
↔ Required Answer
Similar questions
Math,
3 months ago
Math,
3 months ago
History,
3 months ago
Science,
6 months ago
Social Sciences,
1 year ago